1996
DOI: 10.1063/1.869113
|View full text |Cite
|
Sign up to set email alerts
|

Retarded motion of bubbles in Hele–Shaw cells

Abstract: Simulation of the threedimensional behavior of an unsteady large bubble near a structure AIP Conf.The motion of bubbles in a Hele-Shaw cell driven by a surrounding fluid or by gravity has been studied. Assuming that the surrounding fluid wets the solid wall and that the bubble surface is rigid due to the surfactant influence, the translational velocity of an elliptic bubble is estimated. The result indicates that the bubble velocity can decrease by an order of magnitude compared to the prediction of Taylor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 14 publications
2
29
2
Order By: Relevance
“…Apart from the lowest velocities studied, the bubble velocity is lower than the liquid velocity. This has been observed by others [17,18] as well in a Hele-Shaw cell (a narrow gap between parallel plates, comparable to the empty channel) and was attributed to the presence of even minute quantities of surface active impurities in the system. These impurities reportedly stiffen the bubble surface, which hinders the movement of the bubble and increases drag on the bubble.…”
Section: Bubble Velocitymentioning
confidence: 76%
“…Apart from the lowest velocities studied, the bubble velocity is lower than the liquid velocity. This has been observed by others [17,18] as well in a Hele-Shaw cell (a narrow gap between parallel plates, comparable to the empty channel) and was attributed to the presence of even minute quantities of surface active impurities in the system. These impurities reportedly stiffen the bubble surface, which hinders the movement of the bubble and increases drag on the bubble.…”
Section: Bubble Velocitymentioning
confidence: 76%
“…In the later experiments by Kopf-Sill and Homsy 10 , the bubble velocity was observed to be about an order of magnitude lower than the Taylor-Saffman prediction. Possible reasons for the discrepancy have been explored, such as an excessive drag due to a moving contact line within the film and Marangoni effects due to surfactant transport [13][14][15] , yet the underlying mechanisms responsible for the low mobility of the bubble is still not fully understood. In the limit when the 2D droplet is perfectly circular, the Hele-Shaw equations have also been solved analytically by Afkhami and Renardy 16 and Gallaire et al 17 to obtain the droplet velocity for arbitrary viscosity ratios as…”
Section: Introductionmentioning
confidence: 99%
“…According to Maruvada & Park (1996), small bubbles behave according to the criterion /¸1, where is the bubble size and¸is the size of the system (the spot diameter in this case). For laser-generated bubbles is 10\ m, the spot size¸is 2}3;10\ m (or more), which gives /¸1, so that bubbles can be regarded as small and hard spheres.…”
Section: Hydrodynamic Aspect: Bubble Characteristicsmentioning
confidence: 99%
“…It is well known that small bubbles can be approximated by spheres, and that the entire bubble surface may become rigid (Maruvada & Park 1996). Many studies of bubble}bubble collision have shown that the behaviour of bubbles depends on the Reynolds number, Re, and the Weber number, We (Tsao & Koch 1997):…”
Section: Hydrodynamic Aspect: Bubble Characteristicsmentioning
confidence: 99%